Case Report: Primary Thoracic Low-Grade Fibromyxoid Sarcoma in a Young Girl Presenting With Mediastinal Mass Syndrome - Yat Chi Chan; Amanda N. C. Kan; Liz Y. P. Yuen; Innes Y. P. Wan; Kevin K. F. Fung; Yiu-fai Cheung; Yiu-fai Cheung; Karen K. Y. Leung; Dennis T. L. Ku; Anthony P. Y. Liu; Anthony P. Y. Liu (Frontiers in Pediatrics, 2022)
Low-grade fibromyxoid sarcomas (LGFMSs) are typically adult-onset tumors that arise from the extremities. Here, we report an exceptional case of primary thoracic LGFMS in an 8-year-old girl that resulted in mediastinal syndrome. In reporting this case, we discuss the clinical challenges, role of molecular profiling and review reported cases of pediatric thoracic LGFMSs.